ENERGY EFFICIENT HEALTHCARE MONITORING SYSTEM USING 5G TASK OFFLOADING - Sigwele, Tshiamo; Naveed, Arjmand; Hu, Yim-Fun; Ali, Muhammad; Susanto, Misfa (University of Lampung, 2019)
Healthcare expenses can be significantly reduced, and lives saved by enabling the continuous monitoring of patient health remotely using Wireless Body Sensor Networks (WBSN). However, an energy efficient mobile gateway (e.g. 5G smartphone) is required which moves with the patient in real time to process the data from the bio sensors without depleting the battery. This paper proposes a 5G based healthcare cardiovascular disease REmote Monitoring system called 5GREM using Electrocardiogram (ECG) bio sensor as a BSN device. The aim is to monitor and analyse the patient?s heart rhythms and send emergency alerts during irregularities to the nearest caregivers, ambulance or physician to minimise heart attacks and heart failures while saving energy. Since ECG signal execution is computer intensive, requests from the ECG sensor are either executed locally on the gateway, offloaded to nearby mobile devices or to the 5G edge while considering the battery level, CPU level, transmission power, delays and task fail rate